Pengaruh Kualitas Pelayanan Petugas AVSEC terhadap Kepuasan Staf di Security Check Point Bandara International Juanda Sidoarjo - Rahman, Fiqri Maulana; Tamara, Amelia Puspa (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
In addition to the poor quality of information provided by fellow aviation security officers at SCP-1 Juanda International Airport, Sidoarjo, officer activities are also often hampered by frequent miscommunication between aviation security officers and tenant officers and airline officers at the security check point. This will affect staff satisfaction. On this basis, this article examines the effect of service quality on staff satisfaction. The study was conducted using a quantitative method by distributing questionnaires to 100 respondents to collect primary data. Sampling was carried out using the non-probability sampling method. The collected data were then analyzed using simple linear regression, partial test (T test), and coefficient of determination. The results showed that the t-count value was 9.087 (> t table of 1.994) with a significance level of 0.00 (<0.05). The service quality variable has an influence of 54.8% on the level of employee satisfaction.